CsMYB96 confers resistance to water loss in citrus fruit by simultaneous regulation of water transport and wax biosynthesis. (2nd October 2021) - Zhang, Mingfei; Wang, Jinqiu; Liu, Ruilian; Liu, Hai; Yang, Hongbin; Zhu, Zhifeng; Xu, Rangwei; Wang, Pengwei; Deng, Xiuxin; Xue, Shaowu; Zhu, Feng; Cheng, Yunjiang
Abstract : CsMYB96 plays a role in regulating both APQ-mediated water movement and synthesis of cuticular wax to increase tolerance of citrus fruit to water loss. Abstract: A Citrus sinensis R2R3 MYB transcription factor (CsMYB96) has previously been shown to be strongly associated with the expression of many genes related to wax biosynthesis in the fruit. In this study, CsMYB96 was found to alleviate water loss by simultaneously regulating the expression of genes encoding plasma membrane intrinsic proteins ( CsPIP s) and wax-related genes. Expression profiling indicated that CsPIP1;1 and CsPIP2;4 had high expression that was representative of other aquaporins, and they were down-regulated in the peel of post-harvest citrus fruit. CsPIP2;4 was further characterized as the predominant CsPIP, with high expression and high-water channel activity. Transient overexpression of CsPIP2;4 accelerated water loss in citrus fruit. In silico analysis further indicated that the expression of CsMYB96 had a significant negative correlation with that of CsPIP s. In vivo and in vitro experiments confirmed that CsMYB96 was able to directly repress the expression of CsPIP s. In addition, CsMYB96 was able to activate wax-related genes and promote wax biosynthesis for defense against water loss. Transient and stable overexpression of CsMYB96 reduced water loss from both citrus fruit and Arabidopsis.